Las nociones de justicia que construyen las niñas en pleno siglo xxi (2019)
The article is the product of participation in the research center Justicia y Ciudadanía that is part of the research project “Social notions about justice built by children from official schools of Kennedy’s locality in Bogotá DC”. Financed by the Fundación Universitaria Los Libertadores. The topic to approaching is the notions of justice that girls build specifically, emphasized in the social and personal conflict in which they find themselves day by day. The subject is approached from the perspective of authors such as Ralws and Murillo Tordecilla, among others, that deal with the concept of justice and its characteristics.The article is elaborated in order to make gender justice visible and motivate reflection in preschool and primary school teachers of the schools where the research was conducted to find strategies that allow children to understand the importance of women in the immediate contexts in which they live. It is served well to the stipulated in the Ley 1257 de 2008, “so that standards of awareness are dictated, prevention and sanction of forms of violence and discrimination against women, reform of the criminal codes, of criminal procedure, Ley 294 de 1996 and other dispositions are dictated”.